mHealth Apps for Enhanced Management of Spinal Surgery Patients: A Review - Bai, Michael Y.; Mobbs, Ralph J.; Walsh, William R.; Betteridge, Callum (Frontiers in Surgery, 2020)
mHealth (mobile health) refers to mobile technologies that aid medical and public health practices. As of February 2019, 81% of Americans own a smartphone, and mHealth applications (apps) have become increasingly common with more than 400,000 mHealth applications currently available. Advancements in mobile technology now allow us to provide personalized up-to-date information, track personal health data, remind and engage patients, and communicate in a cost-effective way. There are new opportunities for healthcare providers to integrate mHealth into clinical practice. We discuss the current scientific evidence, and research into mHealth technology.